HABILIDADES PARA FACTORIZAR EN LOS ESTUDIANTES DEL PRIMER SEMESTRE DE LA CARRERA PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES, MATEMÁTICAS Y FÍSICA OCTUBRE 2019 - MARZO 2020 - Jácome Cartagena, Hugo Renato (2020)
Research has shown that we must foster skills in students and that the skills set up in the classroom are not always developed, creating disadvantages in their performance. In the study, we were able to explore factoring skills through the application of a test for identifying difficulties in academic performance, For this first, the first semester of the pedagogical career of experimental mathematical and physical sciences was selected as a sample; a test was applied for the collection of data, his study was exploratory, finding out how the students are in factoring; since a questionnaire of knowledge was applied that allowed to explore the abilities and performance of the students to factor, then it became evident what were the most prevalent skills of the students, among the results obtained it was identified that the students of the first semester generate difficulties in factoring; in addition, skills that include identification, recognition of concepts and mathematical properties prevail, also that few students generate skills in heuristic procedures and significantly diminish mathematical skills related to the use of algorithmic procedures, This research revealed that students entering university have problems with factoring and that skills play an important role in the teaching process.